ADAMTS13: An Emerging Target in Stroke Therapy - Chen, Xin; Cheng, Xin; Zhang, Shufan; Wu, Danhong (Frontiers in Neurology, 2019)
Thrombosis is the main pathogenesis of acute ischemic stroke (AIS). The main treatments for stroke either have limited efficacy or increase the risk of bleeding. ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) is a metal protease that can effectively break down VWF (Von Willebrand Factor, VWF), the key factor in thrombus formation. Previous studies have proven that the abnormality of its activity is associated with many diseases. In recent years, it has been found that ADAMTS13 is closely related to stroke. We focus on the relationship between ADAMTS13 and acute ischemic stroke, combining with the structure and function of ADAMTS13 and find that ADAMTS13 is expected to become a new therapeutic target for acute ischemic stroke.